ANALISIS KINERJA DPMPTSP KABUPATEN BLORA DALAM PEMBERIAN LAYANAN PERIZINAN USAHA MIKRO KECIL MENENGAH - Fernando Ghana Dearvigo; Dewi Rostyaningsih; Hesti Lestari (Journal of Public Policy and Management Review, 2023)
This research is motivated by the large number of MSME actors in Blora who do not have business licenses. The purpose of this study was to analyze the performance of the DPMPTSP of Blora Regency in providing licensing services for micro, small and medium enterprises in Blora Regency along with their inhibiting factors. The theory used is the theory of organizational performance by Agus Dwiyanto and the theory of organizational performance by Selim and Woodward. This study uses a qualitative descriptive research method. The results of the study show that the performance of the DPMPTSP of Blora Regency in providing business license services has not gone well. There are performance criteria whose application has not improved, namely service quality criteria, responsiveness criteria, accountability criteria. The criteria that have been implemented quite well are productivity criteria, responsibility criteria, and equity criteria. Then the factors that become obstacles are in the form of a network system, the limited authority of the DPMPTSP relating to other authorities that are outside the authority of the DPMPTSP, human resources employees who have not been able to provide good service to the community. The advice that can be given by researchers is that DPMPTSP must improve the quality of services by various outreach through the media or in person and ball pick-up services so that service procedures become clear, carry out service monitoring and carry out routine evaluations, conduct training for officers on a regular basis, and coordinate with all stakeholders involved so that there is no miscommun